A Model to Evaluate Solubility of Sparingly Soluble Salts in Electrolyte Solutions - M. Abdel-Halim, Hamzeh; A. Issa, Ayman; S. Abu-Surrah, Adnan (Asian Journal of Chemistry, 2016)
A simple model to evaluate the solubility of sparingly soluble salts in aqueous electrolyte solutions at various ionic strengths is presented. The calculations are based on a model presented earlier, which calculates the mean activity coefficient suing an extended Debye-Hückel formulation. Calculations were performed, in aqueous solutions at 25°C, for various salts with concentration range between 0.10-7.0 m. The calculated solubility and the conditional solubility product constant were compared with experimental values reported in literature. Good agreement is observed over a wide range of ionic strength.